Pengaruh Penggunaan Media Flip Chart untuk Meningkatkan Penguasaan Kosakata Bahasa Inggris Siswa di SDN Pitu 2 - Maulana Aziz Nur Rohim; Kartika Septianingrum; Miratu Chaeroh (LP. Ma'arif Janggan Magetan, 2024)
Language learning as a medium of information is very important. English is a language that we must learn and master. The introduction of new words is the most important step in improving one's command of the English language. Using learning media is a great approach to improve vocabulary knowledge in English. Flip chart media is used as a learning tool. Media such as flip charts are useful tools for education because they display information in a format that is visually appealing and easy to digest, allowing students to better remember key ideas, images, symbols, and more. The aim of this research is to find out whether the use of flip chart media can increase the vocabulary acquisition of second grade students at SDN Pitu 2. Quantitative techniques, namely one-group pretest-posttest design, are used in this research. Normality tests and homogeneity tests are research prerequisites; The data is considered normally distributed with a sign value greater than 0.05. A homogeneous sample is a sample whose sign value is greater than 0.05. Research findings show that the use of flip chart media has an impact on students' ability to learn English vocabulary at SDN Pitu 2. This is supported by the results of the paired t-test which has a significance value of 0.000 < 0.05. Thus, it can be concluded that the use of flip chart media can improve students' mastery of English vocabulary at SDN Pitu 2.